Impact of financing sources on palm oil industry in Malaysia - Suzillah Sidek (2011)
Cobb-Douglas production function has been widely used in various sectors and countries. This study applies the production function to examine the influence of financing sources to the production of palm oil in Malaysia. The financing sources are categorizes into two types of credit. The first is private credit which consists of commercial banks credit, merchant banks credit and finance companies credit. The second is public capital credit of which Agro Bank credit is included as a proxy. Public capital credit and export of palm oil are included in the study as additional explanatory variables in the augmented production function. Statistical analyses employed in this study are Ordinary Least Squares (OLS) for multiple regressions, Autoregressive Distributed Lag (ARDL) bound testing approach for co-integration test and Granger causality test with the application of two methods namely Error Correction Model (ECM) based ARDL to test for short run causality and Toda Yamamoto approach to test for long run causality. Time series data used in the study range from the year 1997 to year 2005. The results show that the palm oil industry in Malaysia is experiencing decreasing return to scale and all financing sources except for credit from commercial banks have influence on the production of palm oil in Malaysia.